(untitled) (International Journal of Engineering and Computer Science, 2014)
The solar panel is a highly non-linear source and to select a right operating point on the I-V characteristics based on measured load current and voltage is very crucial in order to obtain maximum output. Several PV Simulation techniques for obtaining right operating point on the I-V characteristics of PV cell are available. In this paper mathematical model of a single diode PV module with different techniques for PV Simulation are briefly presented and compared.